INOVASI PEMBUATAN ROTI MUNGIL DENGAN MENGGUNAKAN METODE PEMBEKUAN ADONAN - Ambawati, Wim; Purnomo, Bambang Heri; Nurhayati, Nurhayati (Cannarium, 2022)
Ã¢â‚¬Å“Mungil BreadÃ¢â‚¬Â is a small bread that is soft and has a lot of filling. This study evaluates the characteristics of the mungil bread produced from frozen dough. This research was conducted using a randomized block design (RBD) which consisted of three factors: storage time, type of liquid milk used, and variations in the amount of egg yolk added to the dough. The type of milk factor used factory milk and fresh milk, while the egg yolk variation factor added to the dough was 8%, 10% and 14%. The measurement result data is expressed in a graph/bar chart accompanied by an error bar. Parameters observed in this study include analysis of physical quality in the form of texture, swelling power, bread volume. Sensory evaluation was carried out by trained panelists with hedonic score tests on color, aroma, taste, texture, and overall parameters. Panelists were asked to rate based on their level of preference. The result of this research innovation is in the form of small bread dough made with the addition of factory milk and 10% egg yolk. Bread dough is still stored well for 4 weeks of storage. The physical properties of the tiny loaves are texture 4.97-5.70 g/mm, flower growth 54-55 ml, growing volume 59.98 - 62.54 cm3.